LncRNA SNHG7 Regulates Mesenchymal Stem Cell Through the Notch1/Jagged1/Hes-1 Signaling Pathway and Influences Folfirinox Resistance in Pancreatic Cancer - Cheng, Dongfeng; Fan, Juanjuan; Qin, Kai; Zhou, Yiran; Yang, Jingrui; Ma, Yang; Shi, Minmin; Jin, Jiabin (Frontiers in Oncology, 2021)
Pancreatic cancer (PC) is one of the deadliest gastrointestinal cancers, accounting for the fourth highest number of cancer-related fatalities. Increasing data suggests that mesenchymal stem cells (MSCs) might influence drug-resistance of GC cells in the tumor microenvironment and play essential roles in drug resistance development. However, the precise underlying process remains a mystery. The purpose of this study was to look at the control of MSC-induced SNHG7 in pancreatic cancer. In vitro and in vivo sphere formation, colony formation, and flow cytometry investigations revealed stemness and Folfirinox resistance in pancreatic cancer cells. To confirm the direct connections between SNHG7 and other related targets, RNA pulldown and immunoprecipitation tests were performed. MSC co-culture enhanced stemness and Folfirinox resistance in pancreatic cancer cells, according to the findings. MSC co-culture increased SNHG7 expression in pancreatic cancer cells, contributing to stemness and Folfirinox resistance. We demonstrated that Notch1 interacted with SNHG7 and could reverse SNHG7's facilitative effect on stemness and Folfirinox resistance in pancreatic cancer cells. Finally, our findings showed that MSCs increased SNHG7 expression in pancreatic cancer cells, promoting stemness and Folfirinox resistance via the Notch1/Jagged1/Hes-1 signaling pathway. These findings could be provider a novel approach and therapeutic target for pancreatic cancer patients.